Effect of plowing depths and type of transmission system on the performance of agricultural tractors under clay soil condition - Mohamed, Mohamed A.; D. Elfadil, Abdelkarim; Muhieldeen, Osama A. (Gezira Journal of Engineering and Applied Sciences, 2018)
The study was conducted at the Experimental Farm of the University of Gedarif during summer season of 2016 at a soil moisture content of 7.24% and bulk density of 1.4 g/cm 3 . Three types of tractors with different transmission systems were used in this study, the transmission systems were conventional, powershift and combination of conventional and powershift. The tested parameters were drawbar power, fuel consumption, wheel slip and field capacity.  To evaluate the tested parameters, three different depths were used, namely, 15, 20 and 25 cm. A completely randomized block design with four replications was used to execute the experiment. The statistical analysis indicated that there was no significant difference (p ≥0.05) between the tractors in drawbar power for the plowing depths of 15 and 20 cm, while there was a significant difference (p ≥0.05) between conventional and the other two tractors for the depth of 25cm; it produced the least power.